Traduzir, traduzir psicanálise - Oliveira, Cibele Regina (2021)
In the specific field of the translation of psychoanalytic texts, this research moves through the current canon in psychoanalytic texts in Portuguese and presents what difficulties the translators have found when dealing with the original text. The objective of this master's research is linked to translation as a practice as it particularly aims at analyzing the difficulties that a translator faces when dealing with texts and works of Psychoanalysis. How are the choices a translator must make usually made? What aspects of both original and target language are at stake? I intend to take the translator’s position as a stepstone, sharing some details of my work translating Henry Krutzen's book into Portuguese: Jacques Lacan Séminaire 1952-1980 - Index Référentiel, 2008, Editora Anthropos highlighting points where reflection was necessary, as well as the support of some resource or theoretical elements that contributed to the translator's decision and position in the face of the impasse. Another point tackled here, as it could not fail to be, I will present discussions raised by the translations of the work of Sigmund Freud, whose influence in the teaching of Lacan - his Return to Freud – embraces Freud’s terminology - the rigor with which Lacan takes the Freudian theory is present in the form of the observation of its terminology in German, which configures a first embarrassment to the translator of the Seminaries. In a way that the constraints present and addressed in several articles about the difficulties in translating the work from German to other languages extend to this present work